Socio-ecological surveys of Apis dorsata in the mountains of the Nilgiri Biosphere Reserve, Western Ghats, India - Rehel, Shiny Mariam; Basavegowda, Mahadesha; Thankiyan, Justinraj; Roy, Pratim (Frontiers in Bee Science, 2024)
This paper provides insights into the ecology and conservation of Apis dorsata (Giant Honey Bee) which are integral to the ecology and livelihoods of those living in the Nilgiri Biosphere Reserve (NBR). Rather than directly comparing nest densities across regions and seasons, our study integrates scientific approaches with Indigenous knowledge to examine changes in nest locations, nesting behaviors, and seasonal patterns across three decades. Social surveys indicate that there has been a decline in wild colony populations over the past 10–20 years. This underscores the critical role of sacred sites and protected areas in conserving Apis dorsata populations. This research aims to inform future conservation strategies and policy frameworks, highlighting the value of interdisciplinary approaches in understanding and preserving wild bee species.